Ambivalent Secularism: Religion, Public Opinion, and the Limits of the Politicization of Faith in Costa Rica: Dossier: VI International Seminar: Latin America. Societies in change. Transformations in religion. - Díaz González, José Andrés (2026)
This article examines the relationship between religious practice, public opinion, and attitudes toward state secularism in Costa Rica. Using data from a nationally representative survey conducted in 2024 (n=1,302), it analyzes how religious affiliation and sociodemographic factors shape views on the role of religion in politics and the public sphere. Logistic regression models show that institutionalized religiosity is associated with lower support for state secularism and greater acceptance of religious presence in public institutions, while higher education reinforces secular orientations. However, broad rejection of the electoral instrumentalization of religion reveals an ambivalent and bounded form of secularism.